2012
DOI: 10.22358/jafs/66144/2012
|View full text |Cite
|
Sign up to set email alerts
|

The effect of inulin on broiler chicken intestinal microflora, gut morphology, and performance

Abstract: This study was conducted to evaluate the effectiveness of inulin on the intestinal microflora, gut morphology, and performance of broiler chickens. After sex identification, 168 male Ross 308 broilers were randomly allotted to 3 treatment groups with 4 replicates and fed for 42 days. Experimental treatments including 0%, 0.5%, or 1% inulin were used. The experimental diets were formulated based on maize-soyabean meal. The results showed that livability and body weight gain were better for broilers fed diets su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
58
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(72 citation statements)
references
References 19 publications
9
58
1
4
Order By: Relevance
“…In studies on farm animals, the addition of prebiotics was found to stimulate the performance of animals, stabilize the microbiome of the digestive tract, and improve animal health status (10,13,15,24,54). On the other hand, other authors did not find such an impact (4,11).…”
Section: Tab 3 Effect Of the Dietary Level Of Two Types Of Inulin (mentioning
confidence: 99%
See 2 more Smart Citations
“…In studies on farm animals, the addition of prebiotics was found to stimulate the performance of animals, stabilize the microbiome of the digestive tract, and improve animal health status (10,13,15,24,54). On the other hand, other authors did not find such an impact (4,11).…”
Section: Tab 3 Effect Of the Dietary Level Of Two Types Of Inulin (mentioning
confidence: 99%
“…Biggs et al (5) proved that feeding a higher level (0.8%) of inulin and short-chain fructo-oligosaccharides depressed growth performance, the digestibility of amino acids, and metabolizable energy in birds. However, there are studies in which even a higher dose was supplemented (1%) (24). Moreover, as reported by Ten Bruggencate et al (44), the rapid fermentation of prebiotics leading to high concentrations of organic acids impaired the barrier function, which reduced the ability of rats to resist salmonella infection.…”
Section: Tab 3 Effect Of the Dietary Level Of Two Types Of Inulin (mentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, they are fermented in the large intestine or colon by beneficial bifidobacteria and other lactic acid producing bacteria, thereby enhancing their relative populations (Pool-Zobel et al, 2002;Roberfroid, 2002;Flickinger et al, 2003). Several dietary grades of inulin are available commercially, and their use as a dietary supplement in animal feed has been shown to enhance growth performance, modulate intestinal microbiota, and improve hematological and immune parameters in fish, poultry, and swine (He et al, 2002;Mahious et al, 2006a;Reza et al, 2009;Ibrahem et al, 2010;Mourino et al, 2012;Nabizadeh, 2012;Ortiz et al, 2013). Nevertheless, the use of inulin as a functional feed additive in the animal feed industry is limited by the cost of the inulin extraction process.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Bailey et al (1991) and Fukata et al (1999) reported that the inclusion of oligofructose in the chicks' diets enabled a substantial reduction of Salmonella colonization in the gastrointestinal tract. Nabizadeh (2012) showed that inulin supplementation caused no significant differences in the microfloral counts of the ileal contents but significantly increased the Bifidobacteria counts and decreased the E. coli counts of the cecal contents. Baurhoo et al (2007) a P/T 6/6 6/6 5/6 5/6 7 2 4/6 3/6 2/6 0/6 out that the mannanoligosaccharides act by blocking the sites of bacterial adhesion, thus reducing the binding capacity of some pathogenic bacteria in the intestinal mucosa.…”
Section: Resultsmentioning
confidence: 94%